Analysis Of The Use Of Village Fund In Stunting Prevention And Treatment - Lawalu, Emiliana Martuti; Leki, Salomon; Pongge, Maria Imakulata; Indrawati, Agnes Susanti (Jurnal Ekonomi, 2024)
Stunting, as a serious issue hindering the growth and development of children and negatively impacting the quality of human resources, has become a major concern in Central Kupang District, East Nusa Tenggara, which ranks fourth in stunting cases. Oelmasi Village and Noelbaki Village, in particular, face significant challenges with a total of 75 cases of stunted children. These villages also encounter serious economic challenges and limited access to healthcare services. This study aims to analyze the implementation of stunting reduction policies in these two villages and evaluate the utilization of village funds to accelerate stunting reduction. A qualitative research method was used, identifying key informants such as health cadres, PKK (Family Welfare Movement) Chairpersons, and mothers of stunted children, as well as supporting informants such as village heads and treasurers. Data were collected through interviews, observations, and document analysis. The results highlight that the approach adopted still emphasizes treatment over prevention. The total budget allocation for Oelmasi Village is IDR 111,992,000 and for Noelbaki Village is IDR 102,300,000, which is used for programs such as integrated health posts, nutrition education, and incentives for cadres. Although village funds have been allocated for stunting reduction, challenges such as budget constraints and ineffective information distribution hinder program optimization. In conclusion, further efforts are needed to enhance public health literacy and strengthen cooperation between local governments and communities in the prevention and treatment of stunting in Oelnasi and Noelbaki Villages.